Conventional sampling plan for green peach aphid, Myzus persicae (Sulzer) (Hemiptera: Aphididae), in bell pepper crops - Carmo, Daiane das Gracas do; Lopes, Mayara Cristina; Araujo, Tamiris Alves de; Ramos, Rodrigo Soares; Silva Soares, Joao Rafael [UNESP]; Paes, Jhersyka da Silva; Picanco, Marcelo Coutinho (Elsevier B.V., 2021)
The green peach aphid Myzus persicae is one of the most important pests in bell pepper crops. Conventional sampling plans are the starting point for the generation of pest control decision-making systems. However, sampling plans have not yet been determined for this pest in bell pepper crops. Thus, the objective of this work was to determine conventional sampling plans feasible for M. persicae in bell pepper crops in the vegetative and reproductive stages. The adequate sample for the evaluation of M. persicae populations in bell pepper plants in the vegetative stage was the 5th most apical leaf. For plants in the reproductive stage, the adequate sample for the evaluation of M. persicae populations was the 3rd most apical leaf. The beating of the apical part of the plants in a white plastic tray was the best technique for sampling M. persicae in bell pepper fields. M. persicae densities adjusted to the negative binomial distribution had a common aggregation parameter (Kcommom = 0.1816). The sampling plan consisted of 158 samples per field. This sampling plan was carried out in 42 min, 57 min and 1 h: 08 min in plots of 1, 5 and 10 ha respectively. The cost of the sampling plan was US$ 1.19, US$ 1.59 and US$ 1.90 for plots of 1, 5 and 10 ha, respectively. The sampling plan developed in this study can be incorporated into integrated pest management programs, as it allows for an adequate assessment of M. persicae populations in bell pepper.
Keywords: Aphids; Sampling unit; Decision-making systems; Control